Analysis of trunk rolling in Parkinson's disease patients using a mattress mobility detection system. (August 2018) - Chiang, Shang-Lin; Lin, Chueh-Ho; Hsu, Yaw-Don; Wei, Shun-Hwa; Sung, Wen-Hsu; Lu, Liang-Hsuan; Chang, Shin-Tsu; Ho, Tsung-Yen; Shen, Yu-Ping; Chen, Liang-Cheng; Lin, Chia-Huei
Highlights: We developed a system to correctly evaluate the trunk rolling ability of PD. The results for PD was significantly poorer than healthy in measures for turning. The mattress mobility detection system can be used in clinic. Abstract: Background and Objective: Parkinson's disease (PD) is a neurodegenerative condition characterized by motor dysfunction and various types of non-motor impairments. The reaction time and movement time are reported to become more severe delayed in worse PD patients. Most tools for evaluating motor impairment are limited by relying on subjective observations and being qualitative in design. The aim of this study was to investigate trunk rolling performance in PD patients by using a recently developed system to detect turning in bed. Methods: The study included 20 PD patients and 42 healthy controls. A mattress mobility detection system was employed for quantitative measurements. Each test session consisted of subjects starting by lying in a supine position on a bed and rolling 10 times onto their left side and 10 times onto their right side. Strain gauges mounted under the feet of the bed recorded changes in the center of pressure (CoP). Results: For turning back, the patients compared with the controls had significantly longer movement time ( P = 0.017), longer time to peak counteraction ( P = 0.001), larger ratio of peak counteraction to movement time ( P = 0.006), shorter CoP displacement ( P < 0.0001), slower turning speed ( P = 0.000), weaker peak counteraction ( P = 0.013), and smaller ratio of peak counteraction to weight ( P = 0.032). Results for turning over were similar except there was no significant difference in the ratio of peak counteraction to weight. Conclusions: The mattress mobility detection system was useful for objectively assessing trunk rolling performance of PD patients. Improved assessment of trunk function in PD patients could lead to better treatments and improved rehabilitation procedures.